Boundaries and continuities: a genealogical approach to some illness representations in Finland - Honkasalo, Marja-Liisa; Hinkkanen, Reea (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Boundaries and continuities: a genealogical approach to some illness representations in Finland